The different faces of biochar: contamination risk versus remediation tool - Hilber, Isabel; Bastos, Ana Catarina; Loureiro, Susana; Soja, Gerhard; Marsz, Aleksandra; Cornelissen, Gerard; Bucheli, Thomas D. (Journal of environmental engineering and landscape management, 2017)
This article reviews the different aspects of biochar as source and sink of organic and inorganic contaminants. Biochar can contain organic contaminants such as polycyclic aromatic hydrocarbons or heavy metals. As the distribution coefficients of the biochar especially for contaminants are high, the freely dissolved concentrations are low and with that also the bioavailability. The link between biochar's inherent contaminants and toxicity to soil meso- and macro-fauna remains unclear, with data being often contradictory and influenced by feedstock and pyrolysis conditions. The biochar's potential to remediate contaminated soils has mainly been addressed in lab studies, but rarely in the field. This far, results have been contradicting. Many studies reported successful immobilization of contaminants but some not. In summary, the ambivalent face of the biochar with regard to contaminants prevails. In future, long term field studies are needed to properly address the sustainability of biochar in this respect.